POLITICAL DEBATES AND THEIR ARTISTIC CONSTRUCTION IN IRAQI SATELLITE CHANNELS ( AN ANALYTICAL STUDY ) : (A research drawn from a Master Thesis) - Ahmed, Ahmed Kareem; Abdul-Razzaq, Adel (ALBAHITH ALALAMI, 2020)
The problem of research on the study of political debate programs in the Iraqi satellite channels, in the "People decide" program by Afaq channel and " electoral competition " by Fallujah channel), and its importance for the community and researchers in the scientific field, as new programs to enter the Iraqi media after we have been the world media a lot in this area at the academic and practical levels (The field), and seeks to find out what the technical construction of the programs of political debates in Iraqi satellite channels and methods of construction and methods of employment used by the technical elements in the presentation of the programs and The study adopted the survey method and the method of analyzing the content which is one of the most appropriate methods of analysis for this research, and the researcher sought to survey the methodological analysis of the two programs,( The people decide in Afaq Channel and an electoral competition in the Fallujah channel ( The researcher chose two programs, The people decide in Afaq channel and an electoral competition in the Fallujah channel.), a sample of the research and set the time period in a comprehensive inventory of all the items of the research sample from 24/3/2018 to 10/5/2018 by 14), A program for (people decide) and from 1/4/2018 until 10/5/2018 with 36 episodes of the program (electoral competition). The research article was in (50) Fifty episodes political debate programs in both channels.